(untitled) (Web of Teachers: Inderscience Research, 2025)
This article provides a comprehensive overview of contemporary hermeneutic approaches in linguistics, tracing the evolution of hermeneutic theory from its classical roots to its current manifestations in modern interpretive practices. The discussion integrates seminal contributions from philosophers such as Gadamer and Ricoeur with recent developments in digital and intercultural communication studies. By exploring how context, tradition, and the dynamic nature of language intersect in hermeneutic inquiry, the article demonstrates the enduring relevance and adaptability of hermeneutics in addressing linguistic complexity in an increasingly globalized and digital era.